Effects of substituting oil palm tree trunk silage for Napier grass silage in total mixed ration on feedlot performance, ruminal fermentation, carcass characteristics and meat quality of crossbred goats - Chuchai, Supinya; Khongpradit, Anchalee; Boonsaen, Phoompong; Sawanon, Suriya (Agriculture and Natural Resources, 2026)
Importance of the work: Commonly, oil palm trunk residues are discarded at the end of the palm’s productive life. However, oil palm trunk silage (OPTS) has potential as an additional roughage source for ruminants. Objectives: To evaluate the levels of substitution of conventional Napier grass silage (NGS) with OPTS in the total mixed ration fed to crossbred goats Materials & Methods: The experiment used 32 crossbred (Boer × Anglo-Nubian) male goats (aged 3 mth) with a mean ± SD initial body weight of 16.50 ± 0.5 kg. The experiment was arranged in a completely randomized design. Equal numbers of goats were assigned randomly to four treatment diets (8 goats per treatment) containing different OPTS to-NGS percentages up to 45% of the total mixed ration diet: 1) 0:45 (NGS); 2) 15:30 (15OPTS); 3) 30:15 (30OPTS); and 4) 45:0 (45OPTS). After being fed the respective diet for 90 d, the animals were slaughtered and evaluated for feedlot performance, ruminal fermentation, blood metabolites, carcass characteristics and meat quality. Data were analyzed using orthogonal polynomial contrasts to test linear, quadratic and cubic responses to roughage levels. Results: Dry matter intake, nutrient intake and average daily gain decreased with increasing OPTS levels (p < 0.05). Ruminal pH, ammonia nitrogen (NH3-N), short-chain fatty acids, blood urea nitrogen, blood glucose and hematocrit were not affected by the treatments. OPTS substitution had no negative impact on carcass characteristics and meat quality. Main finding: OPTS could be substituted for NGS at inclusion levels below 30% dry matter content of the roughage in the total mixed ration diet.